2021
DOI: 10.1080/1828051x.2021.1906165
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation with rosemary oil on methanogenic bacteria density, blood and rumen parameters and meat quality of fattening lambs

Abstract: This study aimed to determine the effect of rosemary (Rosmarinus officinalis) essential oil (REO) in lamb fattening diets on blood, rumen parameters, fattening performance and meat quality. Thirty Norduz male lambs weaned at 4 months of age with average body weight 22.0 ± 4.41 kg were used. Lambs were divided into three groups: no rosemary oil (control, R0), with 250 mg/kg DM (R250) and with 500 mg/kg DM (R500) rosemary oil added to the basal ration, and fed for 70 d. The daily feed intake of the R500 lambs (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…This could improve the health status of the animals and consequently increase their productive performance. In addition, previous studies [56,58] have shown that in lambs the dietary inclusion of low doses (50, 80, and 250 mg/kg DM) of EOs increases serum levels of IGF-1 (insulin-like growth factor 1), which is positively correlated with ADG in sheep [59]. For this reason, similar effects of EO consumption in the present study would partially explain the observed improvements in ADG and FCR [59].…”
Section: Growth Performance and Carcass Characteristicssupporting
confidence: 80%
“…This could improve the health status of the animals and consequently increase their productive performance. In addition, previous studies [56,58] have shown that in lambs the dietary inclusion of low doses (50, 80, and 250 mg/kg DM) of EOs increases serum levels of IGF-1 (insulin-like growth factor 1), which is positively correlated with ADG in sheep [59]. For this reason, similar effects of EO consumption in the present study would partially explain the observed improvements in ADG and FCR [59].…”
Section: Growth Performance and Carcass Characteristicssupporting
confidence: 80%
“…So, IGF-1 is an important metabolite to evaluate the nutrient balance. In a study, serum IGF-1 level increased significantly with the supplementation of 250 mg/kg rosemary oil low dose group in lambs (Guney et al, 2021). Besides, in our study IGF-1 levels improved at ORG 500mg/kg group.…”
Section: Discussionsupporting
confidence: 70%
“…However, in our study total protein and triglyceride concentrations were higher in ORG 500 group than control and other treatment group at 45 th day. Guney et al, (2021) found that glucose and total protein concentrations increased significantly in the dietary supplementation with rosemary oil group. Ran et al, (2018) claimed that plasma glucose, NEFA and BHBA concentrations can be used indicator of energy balance in ruminants.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the increasing propionate concentrate points toward the potential of RE supplementation to lower the production of hydrogen, the electron donor in methanogenesis. However, few studies have been conducted on the methane emissions after RE supplementation in dairy cows and different forms of rosemary had different impacts on rumen methanogens in sheep and goats [ 55 , 56 ]. Thus, further studies are needed to investigate the role of RE in methane emissions.…”
Section: Discussionmentioning
confidence: 99%